2011
DOI: 10.1155/2011/650415
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Performance of Actuators in an Active Orthosis for the Upper Extremities

Abstract: The aim of the project OrthoJacket is to develop a lightweight, portable, and active orthosis for the upper limps. The system consists of two special designed fluidic actuators which are used for supporting the elbow function and the internal rotation of the shoulder. A new design of flexible fluid actuator (FFA) is presented that enables more design options of attaching parts, as it is allowed by conventional actuators with a stationary centre of rotation. This advantage and the inherent flexibility and the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…It was found that important performance requirements are compliance [37,43,68] ; high specific power [38,42] and force [35,45] ; natural motion characteristics [33,36,63,64] ; infinitely variable backdrivability [15,48,64,75] ; ease of control [15,26,39,58] ; and efficiency [63] . Key physical requirements include low mass [47] , slim form [23,29,48,61,63] , low cost [14,40] , modularity [15,22,33,47] , environmental compatibility [28,68] , and quietness [40] . Lastly, significant safety requirements are sanitary cleanliness [68] ; safe exposed parts [33,38,46,52] ; and limited range of motion (ROM), speed, and force [43] .…”
Section: Orthosis Actuator Requirementsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was found that important performance requirements are compliance [37,43,68] ; high specific power [38,42] and force [35,45] ; natural motion characteristics [33,36,63,64] ; infinitely variable backdrivability [15,48,64,75] ; ease of control [15,26,39,58] ; and efficiency [63] . Key physical requirements include low mass [47] , slim form [23,29,48,61,63] , low cost [14,40] , modularity [15,22,33,47] , environmental compatibility [28,68] , and quietness [40] . Lastly, significant safety requirements are sanitary cleanliness [68] ; safe exposed parts [33,38,46,52] ; and limited range of motion (ROM), speed, and force [43] .…”
Section: Orthosis Actuator Requirementsmentioning
confidence: 99%
“…As a guideline, for the orthosis to be comfortably worn all day, its total unsupported or unpowered mass (of which the actuator is only one part) located on the torso, each foot, or in each hand needs to be less than 15%, 1.25%, or 3.75% of the user's body weight respectively [80,81] . A slim actuator form is essential for an orthosis that does not impede its user's motion [61] and is able to be integrated with [47] or hidden under one's clothing. Users appreciate the unobtrusiveness of a slim form-fitting orthosis [48,82,83] .…”
Section: Safetymentioning
confidence: 99%
See 1 more Smart Citation